Development of a Teachmint-Based Digital Module to Improve Students’ Learning Effectiveness in Pancasila Education - Ni Wayan Sayuwaktini Sayu; Rangga Firdaus; Herpratiwi; Undang Rosidin (Didaktika: Jurnal Kependidikan, 2025)
This study aims to analyze (1) the potential and conditions of development, (2) the process, (3) the product, and (4) the attractiveness of teachmint-based digital modules for students. The research method adapts Borg and Gall's research and development (R&D) with a population of class VIII students and a sample of 60 students. Data collection was done using questionnaires, observations, questionnaires, and documentation, while data analysis was done using descriptive statistical analysis techniques and t-tests. The results of the study show: (1) the potential and conditions of module development based on expert validation obtained very valid results and can be used without revision, with a percentage of material experts 90%, media experts 77.5%, and design experts 76%. (2) The process of developing teachmint-based digital learning modules showed an effectiveness level of 91%, which is included in the very effective category. (3) The product of developing teachmint-based digital learning modules has proven to be effective in improving learning outcomes with an effect size value of